AL-KASAI WITH SHEIKH HAMZA( MAY ALLAH HAVE MERCY ON THEM ) COLLECT and GUIDE - Khalaf , Shallal (Islamic Sciences Journal, 2023)
The science of reading is regarded to be one of important sciences from the important sciences of fundamentalists and interpreters and all scientists of the Islamic nation, and this study deserves to be noticed since it can have connection with meaning. does not end, and here we students of science try to catch up with these scientists perhaps we contribute a little, or have the benefit of their knowledge that they left us, gold helped me to carry out this study, asking the Almighty to make it in the balance of our advantages, although it is the effort of the study focused on words that are not read in two different ways . the study also concentrated on the Quranic words in which kissaey differs with hamza on them , so as not to weigh the margins, and i explained the approval readings and infraction of Al-imam Al-kissaey In the margin According to the need the study is divided into two topics: the first one is the Basie element of the study , the second is concerned with words and the way they are reading of the margin to clarify, and attributed Quranic readings to their sources, with extraction the Quranic verses in the margin as the habit of researchers, and the most important results of the research that what is contrary to readers each other is the facilitation that Allah gave to this nation, and not the weakness or abnormality of those reading . The Study depended on honest sourees besides other colleagus helped the researcher in different ways, s as t carry out the study . the study also proved that the selective words from the Quran were relevant to the corect way which was followed by the most important icnowled geables in correct Readings of the Quranic Words